Ionomer-free ultra-low noble metal carrying capacity membrane electrode as well as preparation method and application thereof

Through the anode catalyst slurry and pulse Joule heat treatment without PFSA ionomer, ultra-low precious metal load membrane electrodes were prepared, which solved the problems of high loading and uneven conduction of precious metals, achieved efficient proton and electron transport, and improved the performance and stability of the membrane electrode.

CN120465058APending Publication Date: 2025-08-12CHONGQING UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202510597867.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-05-09
Publication Date
2025-08-12

AI Technical Summary

Technical Problem

The high load of noble metals in existing membrane electrodes leads to poor economics, low catalyst utilization, and PFSA ionomers affect proton and electron conduction, resulting in insufficient performance and stability.

Method used

Using anode catalyst slurry without PFSA ionomer, the ACL-PEM interface contact was improved by pulsed Joule heat treatment to prepare ultra-low precious metal load membrane electrodes.

Benefits of technology

The utilization rate and stability of the catalytic layer are improved, efficient diameter transfer between protons and electrons is achieved, and the use of precious metals is reduced, while maintaining excellent electrolytic performance and long-term stability under ultra-low iridium load.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120465058A_ABST
    Figure CN120465058A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ionomer-free ultra-low noble metal loading capacity membrane electrode, which comprises the following steps: carrying out pulse Joule heat treatment on a proton exchange membrane provided with ionomer-free anode catalyst slurry; according to the method, the pulse Joule heat treatment is carried out on the MEA without adding the PFSA ionomer on the anode catalyst layer, ACL-PEM interface contact is improved through an instantaneous high-temperature field of the pulse Joule heat, the utilization rate of the catalyst layer is increased, the average thickness of the catalyst layer is reduced to 58% of the original thickness, and meanwhile stable combination of the PFSA-free ionomer anode catalyst layer is guaranteed. Tests show that the MEA-IF still has the current density of 2.5 A cm <-2 > under the ultra-low iridium loading capacity of 0.2 mg cm <-2 >, and 2300-hour durability tests show that the voltage attenuation rate of the MEA-IF is only 5.1 mu V.h <-1 >, and the MEA-IF has excellent long-acting stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of electrolytic electrodes, and in particular relates to an ionomer-free ultra-low noble metal loading membrane electrode and a preparation method and application thereof. Background Art

[0002] In the research and application of water electrolysis and fuel cell technologies, the performance of the catalyst layer in the membrane electrode (MEA) plays a crucial role in overall efficiency and stability. Membrane electrode water electrolysis (PEMWE) and proton exchange membrane fuel cells (PEMFC) are considered key technologies for the development of green hydrogen energy and efficient energy conversion, and are important components for achieving the transition to a sustainable energy system. In PEMWE, the anode catalyst layer (ACL) needs to efficiently catalyze the oxygen evolution reaction (OER), while in PEMFC, the catalyst layer needs to promote the oxygen reduction reaction (ORR) and hydrogen oxidation reaction (HOR). However, for both PEMWE and PEMFC, the use of high noble metal loadings (such as Ir and Pt) in the catalyst layer seriously restricts the economic viability of the technology. As the noble metal loading decreases, the uneven distribution of catalysts in traditional MEAs can easily lead to a reduction in active sites and reduced catalyst utilization, which can cause interfacial contact failure and affect overall performance and durability.

[0003] Furthermore, perfluorosulfonic acid (PFSA) ionomers are commonly used as proton-conducting media in the catalytic layer to provide proton pathways. However, the electronic insulation of PFSA ionomers makes it difficult to balance proton and electron conduction within the catalytic layer, limiting catalyst performance. In PEMWEs, the chemical adsorption of PFSA ionomers can also poison IrO2 surface active sites, exacerbating kinetic losses. In PEMFCs, PFSA can lead to localized uneven proton conduction, affecting reaction rates. Literature studies have shown that when the catalytic layer thickness is sufficiently thin and the catalyst particles are closely spaced, protons can be transferred via water molecules (H2O) as a medium, achieving efficient proton conduction. Based on this mechanism, the PFSA ionomer can be directly removed by designing an ultrathin catalytic layer, resolving the problem of balancing proton and electron conduction while simultaneously reducing precious metal loading and improving catalyst utilization. Therefore, developing a high-efficiency catalytic layer system without PFSA ionomers and achieving the synergistic optimization of ultra-low precious metal loading and high durability has become a bottleneck that urgently needs to be overcome in the PEMWE and PEMFC fields. Summary of the Invention

[0004] The present invention aims to address, at least to some extent, one of the technical problems in the related art. To this end, the main purpose of the present invention is to provide an ionomer-free, ultra-low noble metal loading membrane electrode and a preparation method, aiming to address the high cost and low catalytic efficiency of existing membrane electrodes.

[0005] The present invention also discloses the application of the ionomer-free and ultra-low noble metal loading membrane electrode in the fields of water electrolysis for hydrogen production and fuel cells.

[0006] The purpose of the present invention is achieved through the following technical solutions:

[0007] A method for preparing an ionomer-free membrane electrode with ultra-low metal loading comprises subjecting a proton exchange membrane provided with an ionomer-free anode catalyst slurry to pulse Joule thermal treatment to obtain the ionomer-free membrane electrode with ultra-low metal loading.

[0008] In certain specific embodiments, the method further comprises subjecting the proton exchange membrane provided with the cathode catalyst slurry without ionomer to a pulsed Joule heating treatment.

[0009] In certain specific embodiments, the anode catalyst slurry includes a noble metal catalytic material, an organic solvent, and water.

[0010] In certain specific embodiments, the mass concentration of the noble metal catalytic material in the anode catalyst slurry is 15-55%, wherein the ratio of water to organic solvent is (0.5-5): (1-10).

[0011] Furthermore, the noble metal catalytic material includes but is not limited to at least one of iridium oxide, iridium alloy, and ruthenium oxide, and the organic solvent includes but is not limited to at least one of n-propanol, ethanol, isopropanol, and ethylene glycol.

[0012] In certain specific embodiments, the cathode catalyst layer comprises a noble metal catalyst material, a perfluorosulfonic acid resin solution, an organic solvent, and water.

[0013] In certain specific embodiments, the mass concentration of the noble metal catalytic material in the anode catalyst is 10-35%, the mass concentration of the Nafion solution is 5-25 wt%, and the mass ratio of water to the organic solvent is (2-8): (1-5).

[0014] Furthermore, the noble metal catalytic material includes but is not limited to platinum nanoparticles and platinum alloys, and the organic solvent includes but is not limited to at least one of n-propanol, ethanol, isopropanol, and ethylene glycol.

[0015] In certain specific embodiments, the process conditions of the pulse Joule heat treatment include but are not limited to: a pulse current of 1-10 A, a pulse number of 1-15 times, and a duration of each pulse of 1-50 s.

[0016] In certain specific embodiments, the anode catalyst slurry and / or cathode catalyst slurry is attached to the proton exchange membrane by coating or casting.

[0017] As the same inventive concept, the present invention also provides an ionomer-free ultra-low metal loading membrane electrode prepared by the preparation method.

[0018] As the same inventive concept, the present invention also provides the application of the ionomer-free ultra-low metal loading membrane electrode in the field of water electrolysis to produce hydrogen and fuel cells.

[0019] Compared with the prior art, the present invention has at least the following advantages:

[0020] 1) The preparation method of the present application performs pulsed Joule heating on the MEA without PFSA ionomer added to the anode catalyst layer. The instantaneous high temperature field of the pulsed Joule heating improves the ACL-PEM interface contact and improves the utilization rate of the catalyst layer. The average thickness of the catalyst layer is reduced from 1.2μm to 0.7μm, while ensuring the stable bonding of the PFSA ionomer-free anode catalyst layer; at the same time, the flatness of the catalyst layer is improved.

[0021] 2) The ionomer-free ultra-low metal loading membrane electrode prepared in the present application has a catalytic layer system without ionomers. Due to the reduced anode load, the proton transmission distance is shortened, so it can be directly transmitted through the water channel; the electrons are efficiently conducted in the plane through the catalyst particles, forming a separate path transmission of protons and electrons; among them, the in-plane conductivity of MEA-IF is reduced by 33.6% compared with the traditional membrane electrode MEA-AP; the proton transmission resistance is reduced by 16.5%.

[0022] 3) The membrane electrode of this application has achieved a performance breakthrough at ultra-low iridium loading: the optimized MEA-IF is 0.2mgcm -2 2.5A cm-2 was achieved at ultra-low iridium loading -2 , compared with MEA-AP (1.9V@2.0Acm -2 ) increased by 20%; at the same time, after 2300 hours of durability testing, the voltage decay rate of MEA-IF was only 5.1μV·h -1 , which verified that the MEA without ionomer system can operate stably for a long time. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] In order to more clearly illustrate the specific embodiments of the present invention, the following briefly introduces the drawings required for the specific embodiments or the description of the prior art.

[0024] Figure 1 This is a graph showing the bonding strength test between the anode catalyst layer and the PEM in the ionomer-free ultra-low metal loading membrane electrode and the conventional membrane electrode;

[0025] Figure 2 The microscopic morphology of the anode catalyst layer in the ionomer-free ultra-low metal loading membrane electrode and the common membrane electrode in the present invention;

[0026] Figure 3 This is a cross-sectional morphology diagram of the anode catalyst layer in the ionomer-free ultra-low metal loading membrane electrode and the common membrane electrode in the present invention;

[0027] Figure 4 Schematic diagram of mass transport of the ionomer-free ultra-low metal loading membrane electrode and the ordinary membrane electrode in the present invention;

[0028] Figure 5 Polarization curves of the membrane electrode without ionomer and ultra-low metal loading and the common membrane electrode in the present invention;

[0029] Figure 6 This is the durability test results of the membrane electrode with ultra-low metal loading without ionomer and the ordinary membrane electrode in the present invention. DETAILED DESCRIPTION

[0030] The present invention will be further described in detail below with reference to the accompanying drawings and examples. The following examples are merely illustrative and non-restrictive, and should not be used to limit the scope of protection of the present invention.

[0031] When expressing a certain amount, concentration or other value or parameter in the form of a range, preferred range, or preferred upper and lower numerical limits, it should be understood that it is equivalent to specifically disclosing any range by combining any pair of upper range limits or preferred numerical values with any lower range limit or preferred numerical value, without considering whether the range is specifically disclosed. Unless otherwise indicated, the numerical range values listed herein include the endpoints of the range and all integers and fractions within the range.

[0032] Unless otherwise indicated, all percentages, parts, ratios, etc. herein are by weight.

[0033] The materials, methods, and examples herein are illustrative and, unless otherwise indicated, are not to be construed as limiting.

[0034] In the following examples, the proton exchange membrane used is a commercial Nafion N115 membrane; the noble metal catalytic material used in the anode catalyst slurry is iridium oxide; the noble metal catalytic material used in the cathode catalyst slurry is platinum nanoparticles, specifically Pt / C powder (40wt%, Johnson Matthey); the Nafion solution used is purchased from Dupont, and its mass concentration is 5wt%.

[0035] Example 1

[0036] This embodiment provides a method for preparing an ionomer-free membrane electrode with ultra-low noble metal loading, which comprises the following steps:

[0037] 1) Prepare anode catalytic slurry

[0038] 15% IrO2, 37% n-propanol, and 48% deionized water were mixed to obtain an anode catalyst slurry;

[0039] 2) Preparation of cathode catalytic slurry

[0040] 10% Pt / C powder, 48% n-propanol, 28% deionized water and 18% Nafion solution were mixed to obtain a cathode catalyst slurry;

[0041] 3) Spraying proton exchange membrane

[0042] The anode catalyst slurry and cathode catalyst slurry were directly sprayed onto the surface of the proton exchange membrane using ultrasonic spraying method. The spraying feed rate was 0.3 mL min -1 , the heating plate temperature is 90°C; during the spraying process, the cathode is sprayed first and then the anode. After the cathode spraying is completed, it is dried for 30 minutes before the anode spraying is performed to ensure that the n-propanol in the catalytic layer is completely volatilized to obtain a proton exchange membrane coated with a catalytic layer.

[0043] 4) Heat treatment

[0044] The proton exchange membrane coated with the catalyst layer was placed on a carbon cloth and fixed in a Joule heating device using a specific fixture. The pulse current and pulse number were set to 1A and 15 times respectively. Then, a pulse Joule heating treatment was performed, each lasting 45 seconds. The membrane electrode with ultra-low metal loading was obtained. The IrO2 loading in the anode catalyst layer of the membrane electrode was 0.2 mg / cm 2 The Pt / C powder loading in the cathode catalyst layer is 0.04 mg / cm 2 .

[0045] Example 2

[0046] This embodiment provides a method for preparing an ionomer-free membrane electrode with ultra-low metal loading, which comprises the following steps:

[0047] 1) Prepare anode catalytic slurry

[0048] 32% IrO2, 29% n-propanol, and 39% deionized water were mixed to obtain an anode catalyst slurry;

[0049] 2) Preparation of cathode catalytic slurry

[0050] 21.7% Pt / C powder, 40.6% n-propanol, 21% deionized water and 16.7% Nafion solution were mixed to obtain a cathode catalyst slurry;

[0051] 3) Spraying proton exchange membrane

[0052] The anode catalyst slurry and cathode catalyst slurry were directly sprayed onto the surface of the proton exchange membrane using ultrasonic spraying method. The spraying feed rate was 0.3 mL min -1 , the heating plate temperature is 90°C; during the spraying process, the cathode is sprayed first and then the anode. After the cathode spraying is completed, it is dried for 30 minutes before the anode spraying is performed to ensure that the n-propanol in the catalytic layer is completely volatilized to obtain a proton exchange membrane coated with a catalytic layer.

[0053] 4) Heat treatment

[0054] A proton exchange membrane coated with a catalyst layer was placed on a carbon cloth and fixed in a Joule heating device using a specific fixture. The pulse current and pulse number were set to 4A, 10 times, respectively. Then, a pulse Joule heating treatment was performed, each lasting 10 seconds. This resulted in an ionomer-free, ultra-low metal loading membrane electrode (denoted as MEA-IF). The IrO2 loading in the anode catalyst layer of the membrane electrode was 0.2 mg / cm 2 The Pt / C powder loading in the cathode catalyst layer is 0.04 mg / cm 2 .

[0055] Example 3

[0056] This embodiment provides a method for preparing an ionomer-free membrane electrode with ultra-low metal loading, which comprises the following steps:

[0057] 1) Prepare anode catalytic slurry

[0058] 55% IrO2, 19% n-propanol, and 26% deionized water were mixed to obtain an anode catalyst slurry;

[0059] 2) Preparation of cathode catalytic slurry

[0060] 35% Pt / C powder, 30% n-propanol, 15% deionized water and 20% Nafion solution were mixed to obtain a cathode catalyst slurry;

[0061] 3) Spraying proton exchange membrane

[0062] The anode catalyst slurry and cathode catalyst slurry were directly sprayed onto the surface of the proton exchange membrane using ultrasonic spraying method. The spraying feed rate was 0.3 mL min -1 , the heating plate temperature is 90°C; during the spraying process, the cathode is sprayed first and then the anode. After the cathode spraying is completed, it is dried for 30 minutes before the anode spraying is performed to ensure that the n-propanol in the catalytic layer is completely volatilized to obtain a proton exchange membrane coated with a catalytic layer.

[0063] 4) Heat treatment

[0064] The proton exchange membrane coated with the catalyst layer was placed on a carbon cloth and fixed in a Joule heating device using a specific fixture. The pulse current and pulse number were set to 10A, 2 times, and then pulse Joule heating treatment was performed, each lasting 2 seconds. The membrane electrode with ultra-low metal loading was obtained. The IrO2 loading in the anode catalyst layer of the membrane electrode was 0.2 mg / cm 2 The Pt / C powder loading in the cathode catalyst layer is 0.04 mg / cm 2 .

[0065] Comparative Example 1

[0066] This comparative example provides a method for preparing a membrane electrode, which is basically the same as Example 2, except that a component separator is added to the preparation of the anode catalytic slurry, specifically:

[0067] 1) Prepare anode catalytic slurry

[0068] 32% IrO2, 22.4% n-propanol, 31% deionized water and 14.6% Nafion solution were mixed to obtain an anode catalyst slurry;

[0069] The remaining steps 2), 3) and 4) are the same as those in Example 2; the prepared membrane electrode (denoted as MEA-AP) has an IrO2 loading of 0.2 mg / cm2 in the anode catalyst layer of the membrane electrode. 2 The Pt / C powder loading in the cathode catalyst layer is 0.04 mg / cm 2 .

[0070] Performance testing:

[0071] In the following test examples, unless otherwise specified, MEA-IF is based on the sample prepared in Example 2, and MEA-AP is based on the sample prepared in Comparative Example 1.

[0072] 1) The combination of anode catalyst layer and PEM

[0073] Materials and test methods: This application uses the scratch method to characterize and analyze the bonding between the MEA-IF anode catalyst layer and the PEM. The equipment used is a micron scratch tester (CSM MST, Switzerland);

[0074] For the MEA-AP and MEA-IF comparison samples, the experiment precisely controlled the probe's lateral movement while simultaneously applying a progressive normal load. During the test, the first 25μm of probe displacement corresponded to the ACL region, while the last 75μm corresponded to the PEM region. This allowed for the decoupled characterization of interfacial bonding strength and substrate material properties.

[0075] The experimental results are as follows Figure 1As shown in the figure, it can be seen from the data that in the ACL area test stage, the dynamic friction coefficient of the MEA-IF sample is significantly greater than that of the MEA-AP. The significant increase in the friction coefficient directly reflects the enhanced anti-delamination ability of the material interface, further confirming the interfacial adhesion of the membrane electrode in this application, and highlighting the structural robustness and durability of the MEA-IF.

[0076] 2) Micromorphology of the anode catalyst layer in the membrane electrode

[0077] This application uses a focused ion beam-scanning electron microscope system (FIB-SEM, Thermo Scientific Helios G4 UX) for cross-scale structural reconstruction. First, the membrane electrode sample to be tested was frozen and ultrathinly sliced, and a 5nm thick Pt protective layer was deposited on its surface using an ion beam sputtering instrument (Leica ACE600) to avoid amorphization damage during ion beam etching. Subsequently, a 30kV Ga + The ion beam is focused on the selected area (20×20×10μm 3 ) were sliced layer by layer (50 nm slice thickness), and SEM images of each layer were acquired simultaneously with a backscattered electron detector (BSE) at a resolution of 1 nm, resulting in a total of 200 consecutive cross-sectional images. Three-dimensional reconstruction of the image sequence was performed using Avizo 2022.1 software.

[0078] The SEM images are as follows Figure 2 As shown. Among them, Figure 2 (a) and Figure 2 (b) shows that the anode catalyst layer of the MEA-AP sample (Comparative Example 1, the same below) exhibits significant structural heterogeneity, with multiple discrete micron-sized voids (yellow-marked areas) observed in the high-magnification SEM image. This structural defect is primarily due to interfacial contact failure caused by reduced IrO2 catalyst loading, which significantly reduces the PTL-ACL contact area and the resulting reduced ACL surface flatness. This situation may lead to the loss of a conductive network between the catalysts, reducing the in-plane conductivity within the catalyst layer.

[0079] The MEA-IF sample treated with pulsed Joule heat in this application (Example 2, the same below) exhibited a significantly optimized microstructure ( Figure 2 (c) and Figure 2 (d)). At the same observation scale, the surface density of the catalytic layer is improved. Structural analysis shows that the high-temperature, localized melting and recrystallization process induced by transient pulse Joule heating effectively eliminates interfacial contact defects. This application reveals the structural regulation mechanism of pulsed Joule heating in an ionomer-free system at the microscale, improving the uniformity of the anode catalyst layer at low loadings and reducing the presence and adverse effects of micron-scale voids.

[0080] 3) Cross-sectional morphology of the anode catalyst layer of the membrane electrode of the present application

[0081] This application uses liquid nitrogen brittle fracture method to prepare sample cross sections and uses high-resolution SEM to analyze the structure of the anode catalyst layer of MEA-AP and MEA-IF.

[0082] The results are as follows Figure 3 As shown, Figure 3 (a) and Figure 3 (b) shows that in the conventionally prepared MEA-AP sample (Comparative Example 1), the catalytic layer is mainly composed of catalyst, PFSA ionomer and pores; while in the MEA-IF sample (Example 2), the catalytic layer is composed of catalyst and a smaller amount of pores, which presents a typical three-phase composite structure: IrO2 catalyst particles are wrapped by PFSA ionomer to form a loosely stacked layered structure with an average thickness of 1.2±0.15μm. In significant contrast, the MEA-IF sample treated with pulsed Joule heat exhibits a highly densified cross-sectional structure ( Figure 3 (c) and Figure 3 (d)). Accurately measured, the average thickness of the catalytic layer decreased to 0.7±0.05 μm (a 41.7% decrease). This structural evolution stems from the absence of PFSA ionomers in the MEA-IF anode catalytic layer and the characteristic undulating morphology of the ACL-PEM interface. This application demonstrates, through SEM morphology, that pulsed Joule heating induces melt rearrangement at the ACL-PEM interface, successfully constructing an ionomer-free catalytic layer system with undulating ACL-PEM interface characteristics.

[0083] In summary, this application explains the synergistic enhancement mechanism of proton and electron transport in the PFSA-free ionomer system MEA-IF based on the SEM microstructure characterization results, such as Figure 4 As shown. In the traditional MEA-AP system, proton transport mainly relies on the ionic network of the PFSA ionomer, while electron conduction is achieved through the physical contact of the IrO2 particles. In the MEA-IF system treated with pulsed Joule heat, the ACL-PEM interface corrugated morphology optimizes the interface contact, so the proton transport efficiency of the interface is improved. Secondly, after the thickness of the catalytic layer is reduced to 700nm, the short-distance proton transport in the anode catalytic layer can be completed by water. This discovery is in line with the development needs of PEMWE technology for ultra-low Ir loading. The electron transport of MEA-IF can be directly and efficiently transmitted through IrO2 particles. In this way, separate path transmission of protons and electrons is formed in the anode catalytic layer of MEA-IF. This structure can cleverly separate the transmission of the two, which also greatly increases the material transport efficiency in MEA-IF.

[0084] 4) Electrochemical characterization

[0085] Test samples: Since the IrO2 loading in the anode catalyst layer has a decisive influence on the electrolytic performance, the test samples were prepared with different loadings (0.1, 0.2, 0.3 and 0.06 mg / cm 2 ) MEA-AP (preparation methods of different loadings are the same as those of Comparative Example 1), and different loadings (0.1, 0.2, 0.3 and 0.06 mg / cm 2 ) MEA-IF (the preparation method of different loadings is the same as Example 2);

[0086] This application uses a two-electrode system, with the anode side as the working electrode and the cathode side as the counter electrode and reference electrode. The electrolytic performance of the electrolytic cell was evaluated by LSV testing, the electrochemical active area of the anode catalyst layer was calculated by CV testing, and the high-frequency resistance of different samples was analyzed by constant current EIS testing.

[0087] The results are as follows Figure 5 (a) shows the polarization curve test of the conventional membrane electrode (MEA-AP) with different IrO2 loadings. -2 In the range of 1.9 V, the current density is about 2.0 A cm -2 However, when the IrO2 loading was reduced to 0.06 mg cm -2 When the electrolysis performance decreased significantly, the current density at 1.9 V was only 0.9 A cm -2 , which is much lower than the current density under other loading conditions. This phenomenon is mainly attributed to the PTL-CL interface contact problem caused by the reduction of IrO2 loading: as the thickness of the catalytic layer decreases and the surface flatness decreases, the PTL-CL contact area decreases accordingly, which not only leads to a significant increase in HFR but also causes an increase in activation loss.

[0088] After the pulse Joule heating treatment of the anode catalyst layer without PFSA ionomer, the polarization curve test results of MEA-IF with different IrO2 loadings are as follows: Figure 5 (b) shows that the electrolysis performance has been significantly improved. Among them, the best performance MEA-IF-0.2 has a current density of 2.5A cm at a voltage of 1.9V. -2 , compared with MEA-AP-0.2(1.9V@2.0Acm -2 ) increased by 25%. It is worth noting that when the anode IrO2 loading was reduced to 0.06 mg cm -2 (Total precious metal loading is 0.1 mg cm -2 ), MEA-IF-0.06 can still achieve 2.2A cm -2The current density is higher than that of MEA-AP-0.06 (1.0A cm -2 ) increased by 120%.

[0089] 5) Stability

[0090] Long-term stability is a key indicator for evaluating the comprehensive performance of PEMWE. To this end, this application conducted a 2300-hour durability test on the electrolyzer equipped with MEA-AP (Comparative Example 1) and MEA-IF (Example 2) under the test conditions of 1.0 A cm -2 @80℃;

[0091] The test results are as follows Figure 6 As shown in the figure, MEA-IF not only maintains excellent performance (1.6V@1.0A cm -2 ), the battery voltage growth rate is only 5.1μV h -1 , significantly better than the 132.2μVh of MEA-C electrolyzer -1 .

[0092] At the same time, after the stability test, the dissolved metal ions in the anode circulating water were detected. During long-term operation, due to the high potential and acidic environment of the PEMWE anode, IrO2 may further dissolve into soluble ionic forms, such as Ir 3+ or Ir 4+ .

[0093] The results showed that MEA-IF demonstrated excellent durability and performance, with an extremely low degradation rate over more than 2,000 hours of testing, one-sixth of that of MEA-AP. This excellent performance demonstrates that the ionomer-free and ultra-low precious metal loading membrane electrode prepared in this application has significant application potential.

[0094] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some or all of the technical features therein. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and description of the present invention.

Claims

1. A method for preparing an ionomer-free ultra-low noble metal loading membrane electrode, characterized in that: A proton exchange membrane provided with an anode catalyst slurry containing no ionomer is subjected to pulsed Joule thermal treatment to obtain an ionomer-free ultra-low noble metal loading membrane electrode.

2. The method for preparing an ionomer-free ultra-low noble metal loading membrane electrode according to claim 1, characterized in that: The method also includes subjecting a proton exchange membrane provided with a cathode catalyst slurry that does not contain an ionomer to a pulsed Joule heating treatment.

3. The method for preparing an ionomer-free ultra-low noble metal loading membrane electrode according to claim 2, characterized in that: The anode catalyst slurry includes a noble metal catalyst material, an organic solvent and water.

4. The method for preparing an ionomer-free ultra-low noble metal loading membrane electrode according to claim 3, characterized in that: The noble metal catalytic material includes but is not limited to at least one of iridium oxide, iridium alloy, and ruthenium oxide, and the organic solvent includes but is not limited to at least one of n-propanol, ethanol, isopropanol, and ethylene glycol.

5. The method for preparing an ionomer-free ultra-low metal loading membrane electrode according to claim 2, characterized in that: The cathode catalyst layer comprises a noble metal catalyst material, a perfluorosulfonic acid resin solution, an organic solvent and water.

6. The method for preparing an ionomer-free ultra-low noble metal loading membrane electrode according to claim 5, characterized in that: The noble metal catalytic material includes but is not limited to platinum nanoparticles and platinum alloys, and the organic solvent includes but is not limited to at least one of n-propanol, ethanol, isopropanol, and ethylene glycol.

7. The method for preparing an ionomer-free membrane electrode with ultra-low noble metal loading according to any one of claims 1 to 6, characterized in that: The process conditions of the pulse Joule heat treatment include but are not limited to: a pulse current of 1-10 A, a pulse number of 1-15 times, and a duration of each pulse of 1-50 s.

8. The method for preparing an ionomer-free ultra-low noble metal loading membrane electrode according to claim 1 or 2, characterized in that: The anode catalyst slurry and / or cathode catalyst slurry is attached to the proton exchange membrane by coating or casting.

9. An ionomer-free membrane electrode with ultra-low noble metal loading prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the ionomer-free ultra-low noble metal loading membrane electrode according to claim 9 in the field of water electrolysis for hydrogen production and fuel cells.